Manajemen Rekrutmen Karyawan untuk Meningkatkan Produktivitas Panen Tandan Buah Segar (TBS) di Perusahaan Perkebunan Kelapa Sawit PT “XYZ” (Terapan 8 Langkah Perubahan Kotter) - Muhammad Sapruwan (JURNAL CITRA WIDYA EDUKASI, 2014)
Labor is very beneficial for the company, especially to carry out all operations of the company. With the study of Labor Akad system, it can be concluded that no effect of the implementation of the Labor Akad, both the quantity and quality of the performance improvement / performance especially in operational aspects of the company in the field. The company increased as much as 71% TBS acquisition since the change in labor recruitment system.